PENGARUH BOOK-TAX DIFFERENCES TERHADAP PERSISTENSI LABA PADA PERUSAHAAN YANG TERDAFTAR SEBAGAI ANGGOTA LQ45 DI BURSA EFEK INDONESIA - Nandia Desi Eka Yanti; kusnadi kusnadi (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2018)
This study aims to provide empirical evidence whether the variable Difference Permanent,Temporary Differences, Large Positive Book-Tax Differences, Large Negative Book-Tax Differencesand Return On Equity (ROE) Influential Against Persistence Profit In Company Listed As Members ofLQ45 Indonesia Stock Exchange (BEI). The sample used in this study were 14 companies registered asmembers LQ45 in the Indonesia Stock Exchange which displays audited financial statements duringthe period 2010-2014.The results showed that permanent differences not significantly affect earnings persistence, thetemporary difference does not significantly affect earnings persistence. Variable positive large booktax differences and large negative book tax differences also do not have a significant effect, while thereturn on equity (ROE) significantly affect the earnings persistence. It can be concluded that thepersistence of earnings would be lower if there is a large temporary differences and the persistence ofearnings will increase if there is a large permanent difference. In addition the company with a largepositive book tax differences and large negative book tax differences can not retain earningscompared with companies that have a small book tax differences.